2019
DOI: 10.1038/s41591-019-0424-4
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and transcriptomic profiling expands precision cancer medicine: the WINTHER trial

Abstract: Precision medicine focuses on DNA abnormalities, but not all tumors have tractable genomic alterations. The WINTHER trial () navigated patients to therapy on the basis of fresh biopsy-derived DNA sequencing (arm A; 236 gene panel) or RNA expression (arm B; comparing tumor to normal). The clinical management committee (investigators from five countries) recommended therapies, prioritizing genomic matches; physicians determined the therapy given. Matching scores were calculated post-hoc for each patient, accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
398
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 417 publications
(413 citation statements)
references
References 39 publications
8
398
0
7
Order By: Relevance
“…Recently, Schutte et al showed integration of genomic and transcriptomic data significantly outperformed less comprehensive analysis in the identification of clinically relevant molecular alterations [65]. The combination of DNA and RNA-based analyses have shown to serve as mutual controls for verifying potential findings [21]. As LGSOC is a rare cancer, model systems and patient samples are limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Schutte et al showed integration of genomic and transcriptomic data significantly outperformed less comprehensive analysis in the identification of clinically relevant molecular alterations [65]. The combination of DNA and RNA-based analyses have shown to serve as mutual controls for verifying potential findings [21]. As LGSOC is a rare cancer, model systems and patient samples are limited.…”
Section: Discussionmentioning
confidence: 99%
“…To accelerate progress in precision oncology, future research must go beyond the genomic aberrations found in tumors and explore the more complex aspects of tumor biology. Thus, multiomics tumor profiling with data integration analysis [21] provides a new window of opportunity for the identification of molecular disease drivers leading to more successful drug therapies.…”
mentioning
confidence: 99%
“…There have been significant advances in precision oncology, with an increasing adoption of sequencing tests that identify targetable mutations in cancer driver genes. Aiming to complement these efforts by considering genome-wide tumor alterations at additional "-omics" layers, recent studies have begun to explore the utilization of transcriptomics data to guide cancer patients' treatment [1][2][3][4] . These studies have reported encouraging results, testifying to the potential of such approaches to complement mutation panels and increase the likelihood that patients will benefit from genomics-guided, precision treatments.…”
Section: Introductionmentioning
confidence: 99%
“…High-throughput profiling of transcripts and proteins can identify genes whose expression is altered by a drug of interest [19][20][21]. Transcriptomic profiling on its own does not take into account post-transcriptional modifications, efficiency of translation or transcript turnover, all of which can affect activity of the encoded proteins [22,23]. Therefore combining transcriptomic and proteomic profiling may be more effective for identifying drug-induced changes [24][25][26].…”
Section: Introductionmentioning
confidence: 99%